Health-related quality of life in patients with depression treated with duloxetine or a selective serotonin reuptake inhibitor in a naturalistic outpatient setting - Hong, Jihyung (Patient Prefer Adherence, 2015)
PURPOSE: To assess the levels of quality of life (QoL) in major depressive disorder (MDD) patients treated with either duloxetine or a selective serotonin reuptake inhibitor (SSRI) as monotherapy for up to 6 months in a naturalistic clinical setting mostly in the Middle East, East Asia, and Mexico. PATIENTS AND METHODS: Data for this post hoc analysis were taken from a 6-month prospective observational study involving 1,549 MDD patients without sexual dysfunction. QoL was measured using the EQ-5D instrument. Depression severity was measured using the Clinical Global Impression of Severity and the 16-item Quick Inventory of Depressive Symptomatology Self-Report (QIDS-SR(16)), while pain severity was measured using the pain items of the Somatic Symptom Inventory. Regression analyses were performed to compare the levels of QoL between duloxetine-treated (n=556) and SSRI-treated (n=776) patients, adjusting for baseline patient characteristics. RESULTS: These MDD patients, on average, had moderately impaired QoL at baseline, and the level of QoL impairment was similar between the duloxetine and SSRI groups (EQ-5D score of 0.46 [SD =0.32] in the former and 0.47 [SD =0.33] in the latter, P=0.066). Both descriptive and regression analyses confirmed QoL improvements in both groups during follow-up, but duloxetine-treated patients achieved higher QoL. At 24 weeks, the estimated mean EQ-5D score was 0.90 in the duloxetine cohort, which was statistically significantly higher than that of 0.83 in the SSRI cohort (P<0.001). Notably, pain severity at baseline was also statistically significantly associated with poorer QoL during follow-up (P<0.001). In addition, this association was observed in the subgroup of SSRI-treated patients (P<0.001), but not in that of duloxetine-treated patients (P=0.479). CONCLUSION: Depressed patients treated with duloxetine achieved higher QoL, compared to those treated with SSRIs, possibly in part due to its moderating effect on the link between pain and poorer QoL.